Natural convection in a diagonally divided square cavity filled with a porous medium - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Ioan (Elsevier France-Editions Scientifiques Medicales Elsevier, 2009)
The flow and heat transfer in a diagonally divided square cavity by an inclined plate and filled with a porous medium were numerically analyzed in this paper. Vertical walls are kept at isothermal conditions, while horizontal walls are insulated. A finite difference scheme was used to solve the dimensionless governing partial differential equations along with the corresponding boundary conditions. Computations were Carried out to examine the effects of Rayleigh number (100 <= Ra <= 1000), thermal conductivity ratio between plate and fluid (0.1 <= k <= 10) and the position of the partition (45 degrees, Case 1 and 135 degrees, Case II). It was found that heat transfer is attenuated when the plate is positioned at 45 degrees, the heat transfer is less than when it is at 135 degrees. (C) 2008 Elsevier Masson SAS. All rights reserved.
Keywords: Divided cavity; Natural convection; Porous medium; Numerical results